Antithrombin-independent thrombin inhibitors, but not direct factor Xa inhibitors, enhance thrombin generation in plasma through inhibition of thrombin-thrombomodulin-protein C system - Furugohri, Taketoshi; Sugiyama, Nobutoshi; Morishima, Yoshiyuki; Shibano, Toshiro (Thrombosis and Haemostasis, 2011)
There is increasing concern that some anticoagulants can paradoxically increase thrombogenesis under certain circumstances. Previously, we demonstrated that at certain doses a direct thrombin inhibitor, melag-atran, worsens the coagulation status induced by tissue factor (TF) in-jection in a rat model. We utilised an in vitro thrombin generation (TG) assay to determine if direct thrombin inhibitors could enhance TG in human plasma, and whether inhibition of the negative-feedback sys-tem [thrombin-thrombomodulin (TM)-protein C] contributed to the TG enhancement. TG in human plasma was assayed by means of the cali-brated automated thrombography. In this assay, direct factor Xa (FXa) inhibitors such as edoxaban and antithrombin (AT)-dependent anti-coagulants such as heparin did not increase, but simply suppressed TG. AT-independent thrombin inhibitors (melagatran, lepirudin, and active site blocked thrombin (IIai)) increased peak levels of TG (2.0, 1.6, and 2.2-fold, respectively) in the presence of 12 nM recombinant human soluble TM (rhsTM). Melagatran and lepirudin at higher concentrations began to suppress TG. In the absence of rhsTM, the enhancement of peak TG by melagatran decreased to 1.2-fold. Furthermore, in protein C-deficient plasma, AT-independent thrombin inhibitors failed to enhance TG. In addition, a human protein C neutralising antibody increased the peak height of TG in the presence of rhsTM. These results suggest that AT-independent thrombin inhibitors may activate throm-bogenesis by suppression of the thrombin-induced negative-feedback system through inhibition of protein C activation. In contrast, direct FXa inhibitors are more useful than AT-independent thrombin inhibitors in terms of lower possibility of activation of the coagulation pathway.
Keywords: Thrombin inhibitor; factor Xa inhibitor; protein C; thrombomodulin; negative-feedback system